When virtue is not an option: Decision making in unhealthy food choices. Issue 3 (September 2019) - Trabold Apadula, Lauren; Martins, Chrissy M
Background: Health conscious consumers often make choices from constrained sets of food options, such as a restaurant menu, in which healthy options may not be present. Aim: The aim of this research was to examine how different decision strategies, such as selection versus rejection, influence the food option chosen when a choice set is restricted to unhealthy options. The mediating role of anticipated guilt was also explored. Methods: An experiment was conducted using a hypothetical choice scenario, in which participants were randomly assigned to a decision making strategy (select versus reject), health objective (diet versus indulge), and relative preference for the options (choice between two preferred options versus one preferred and one non-preferred option) was manipulated. Results: When using a selection strategy, consumers are more likely to choose their most preferred option, regardless of their health objectives, but when using a rejection strategy, health conscious consumers are more likely to avoid their most preferred option and consume a lesser liked alternative. Further, this effect is driven by reduced feelings of guilt. Important boundary conditions include consumer preference for the food options, as health conscious consumers will not reject their favorite option if they do not like the alternative. Conclusions: Decision making strategy influences health conscious consumers' choices between unhealthy food options.